2008
DOI: 10.1073/pnas.0805592105
|View full text |Cite
|
Sign up to set email alerts
|

Ecological changes in Miocene mammalian record show impact of prolonged climatic forcing

Abstract: faunal turnover ͉ isotope ecology ͉ mammals ͉ paleocommunities ͉ flood plain paleoecology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 32 publications
4
117
0
Order By: Relevance
“…Such intraspecific evolution may be easier in some lineages than in others (Vrba 1999). The ability to evolve while maintaining a relatively stable range has also been documented in the classic study of Darwin's finches (Grant and Grant 2008), and suggested by recent research on dietary shifts in mammal lineages during Miocene climate change in Pakistan (Badgley et al 2008). This is also consistent with predictions of the variability selection hypothesis of Potts (1998), in which species with the capacity to change rapidly under shifting environmental conditions preferentially survive relative to specialized species lacking this capacity.…”
Section: Discussionsupporting
confidence: 78%
“…Such intraspecific evolution may be easier in some lineages than in others (Vrba 1999). The ability to evolve while maintaining a relatively stable range has also been documented in the classic study of Darwin's finches (Grant and Grant 2008), and suggested by recent research on dietary shifts in mammal lineages during Miocene climate change in Pakistan (Badgley et al 2008). This is also consistent with predictions of the variability selection hypothesis of Potts (1998), in which species with the capacity to change rapidly under shifting environmental conditions preferentially survive relative to specialized species lacking this capacity.…”
Section: Discussionsupporting
confidence: 78%
“…At present, the discontinuous and incomplete paleoenvironmental record renders linkages to diet change weak. This is in contrast to the continuous, multiproxy paleoenvironmental records from 8 to 5 Ma in the Siwalik Hills of India and Pakistan, where a spatiotemporally continuous isotopic record of soil carbonates and a rich, coeval faunal collection, which includes isotope data from enamel, show that long-term climate change resulted in major faunal turnover (12). Building a multiproxy data set from existing East African sites during this time period has the potential of elucidating the primary drivers of herbivore diet change related to changes in paleoenvironment and paleoclimate.…”
Section: Resultsmentioning
confidence: 84%
“…Previously published isotope data on enamel from the Nakali, Namurungule, Nawata, and Nachukui formations (included and expanded significantly here) indicate a shift toward C 4 -dominated diets between 9.6 and 4.2 Ma (7). The previously published fossil enamel δ 13 C record from East Africa shows that herbivores incorporated C 4 vegetation into their diets as early as ∼10 Ma and is generally consistent with the Late Miocene (8-6 Ma) global expansion of C 4 vegetation documented in the Siwaliks, North America, and South America (1,(11)(12)(13)(14).…”
mentioning
confidence: 75%
“…Although temporal changes in terrestrial fossil diversity have been linked to changing productivity and temperature (12)(13)(14), the few quantitative analyses to date have been performed at highly disparate spatial scales, either global to continental or for single fossil locations (15)(16)(17). The evidence for terrestrial diversity-climate relationships from these studies is equivocal, calling into question the universality of the diversity-productivity relationship.…”
mentioning
confidence: 89%